Effectiveness of computerized visual screening tool used in driving schools in Malaysia - Abdul Mutalib, Haliza; Md Mustafa, Md Muziman Syah; Mohammad Fadzil, Norliza (Academy of Family Physicians of Malaysia, 2011)
Purpose: A survey on new Malaysian drivers was conducted in Malaysia between year 2006-2009. The objective of this study was to look at the effectiveness of the present computerized visual screening tool and to compare it with the conventional testing method. Methods: A total of 3717 drivers aged 19±6 years, who had passed in the computerized visual screening, participated in this study. Results: 250 subjects achieved less than 0.3 LogMAR with their best eye and 83 subjects failed the Ishihara Test after retested using the conventional tool. Conclusion: These finding showed the computerized visual screening test failed to filter some subjects according to the standards set.